2022
DOI: 10.1186/s13062-021-00309-3
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR205HG accelerates cell proliferation, migration and invasion in hepatoblastoma through the activation of MAPK signaling pathway and PI3K/AKT signaling pathway

Abstract: Background Hepatoblastoma (HB) is identified to be the most common liver malignancy which occurs in children. Long non-coding RNAs (lncRNAs) have been implicated in numerous biological processes and diseases, including HB. LncRNA MIR205 host gene (MIR205HG) has been investigated in multiple cancers, however, its role in HB remains to be elucidated. Methods MIR205HG expression was analyzed by RT-qPCR. EdU, colony formation and transwell assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(26 reference statements)
0
10
0
Order By: Relevance
“… Cui et al (2019) found that miR-193a-5p directly targets DPEP1 and participates in Hepatoblastoma progression by regulating the expression of the PI3K/Akt/mTOR signaling pathway. The lncRNA MIR205HG has also been reported to accelerate cell proliferation, migration, and invasion in Hepatoblastoma by activating the MAPK and PI3K/AKT signaling pathways ( Zhang et al, 2022 ). Yamamoto et al (2007) suggested that reduced expression of the tumor suppressor p53 could confer resistance to oxidative stress in Hepatoblastoma, partly contributing to its development.…”
Section: Genetics and Hepatoblastomamentioning
confidence: 99%
See 1 more Smart Citation
“… Cui et al (2019) found that miR-193a-5p directly targets DPEP1 and participates in Hepatoblastoma progression by regulating the expression of the PI3K/Akt/mTOR signaling pathway. The lncRNA MIR205HG has also been reported to accelerate cell proliferation, migration, and invasion in Hepatoblastoma by activating the MAPK and PI3K/AKT signaling pathways ( Zhang et al, 2022 ). Yamamoto et al (2007) suggested that reduced expression of the tumor suppressor p53 could confer resistance to oxidative stress in Hepatoblastoma, partly contributing to its development.…”
Section: Genetics and Hepatoblastomamentioning
confidence: 99%
“…The lncRNA MIR205HG is significantly overexpressed in Hepatoblastoma and competitively binds to miRNA-514a-5p to activate the mitogen-activated protein kinase signaling pathway. It also activates the PI3K/AKT signaling pathway, and lncRNA MIR205HG promotes the proliferation, migration, and invasion of Hepatoblastoma by activating both pathways ( Zhang et al, 2022 ). The lncRNA OIP5-AS1 can activate β-catenin signaling by promoting binding between PTBP1 and β-catenin, thereby promoting Hepatoblastoma proliferation and silencing.…”
Section: Epigenetics and Hepatoblastomamentioning
confidence: 99%
“…Meanwhile, MIR205HG also serves as a sponge for miR-205-5p to activate the PI3K/AKT signaling pathway. Taken together, MIR205HG accelerates cell proliferation, migration and invasion in HB through MAPK and PI3K/AKT signaling pathways (118). The expression of NBR2 is significantly increased within HB samples; moreover, under glucose starvation, NBR2 expression is significantly upregulated.…”
Section: Hepatoblastoma (Hb)mentioning
confidence: 88%
“…Similar effects have been observed in ubiquitin specific peptidase 7 (UPS7), an essential component for LC progression and regulation of p53, in that miR-205 acts as an inhibitor of UPS7 and helps channeling p53 into check of cell’s proliferation levels [ 25 ]. Furthermore, when the expression of miR-205 host gene role was investigated, it showed that miR-205-5p activates the pathway signaling of PI3K/AKT and helps in the suppression, migration, proliferation and invasion of hepatoblastoma cells [ 26 ].…”
Section: Role Of Mir-205 In Liver Diseasesmentioning
confidence: 99%